Positive electrode material and preparation method and application thereof
By preparing NiCoS-x and NiCoSP-x positive electrode materials, the problems of low electronic conductivity and slow chemical reaction kinetics of Ni3S4 materials are solved, and the electrochemical performance of high specific capacity, good cycle stability and fast charging and discharge are achieved, which are suitable for supercapacitors.
Patent Information
- Application Number
- CN202510087008.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-22
AI Technical Summary
In the prior art, Ni3S4, as a supercapacitor positive electrode material, has low electronic conductivity and slow chemical reaction kinetics, which limits its performance.
By mixing the nickel source and cobalt source with deionized water, adding Na2S solution and carrying out hydrothermal reaction, NiCoS-x material was obtained, and calcined with NaH2PO2 under atmosphere protection, NiCoSP-x material was prepared to improve its electronic conductivity and reaction kinetics.
The prepared NiCoS-x and NiCoSP-x positive electrode materials exhibit high specific capacity, good cycle stability and fast charging and discharging capabilities, and are suitable for supercapacitors.
Smart Images

Figure CN119864241A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of novel energy storage, and in particular relates to a positive electrode material and a preparation method and application thereof. Background Art
[0002] With the increasing shortage of fossil fuel resources and the intensification of climate change issues, exploring efficient renewable energy conversion technologies and energy storage carriers has become a key topic in the field of scientific research. Supercapacitors, with their excellent charge / discharge efficiency, long cycle life, wide operating temperature range and high specific power characteristics, have shown great potential in the field of energy storage. However, their relatively low energy density is still a major bottleneck restricting their commercial application. Therefore, it is particularly urgent to develop supercapacitor electrode materials with high energy density.
[0003] Transition metal sulfides (TMS), especially Ni3S4, as a new type of Faraday pseudocapacitor cathode material, have attracted much attention due to their abundant resources and environmental friendliness. However, the low electronic conductivity and slow chemical reaction kinetics of Ni3S4 limit its performance.
[0004] There are currently some technologies that attempt to address these challenges, but they all have limitations:
[0005] Although the flower-shaped nickel sulfide prepared by the solvothermal method in patent CN105489390B improves the volume expansion problem and enhances the cycle stability, its specific capacity performance is not outstanding. The specific capacity at a charge and discharge current of 1A / g is only 1350F / g.
[0006] Patent CN117275962A introduced MXene to synthesize MXene / nickel cobalt sulfide electrode materials, which improved conductivity and specific capacitance. However, the complex preparation and high cost of MXene, as well as unstable phenomena such as decomposition or phase change at high temperatures, limit its practical application.
[0007] Patent CN111333129B uses durian peel to prepare porous carbon and nickel sulfide composite materials, which enhances conductivity, power density and cycle stability. However, the preparation process requires two high-temperature calcinations and one hydrothermal treatment, and the process is cumbersome.
[0008] Although the nickel sulfide / carbon nanotube flexible composite film prepared by patent CN109872881B has a high specific capacitance, its voltage window is narrow and hydrogen is required during the CVD preparation process, which poses a safety hazard.
[0009] In addition, there are other technologies for carbon coating Ni3S4 or preparing composite materials. Although they have certain effects, the process is complicated and the cost is high, which is not conducive to industrial production.
[0010] Therefore, there is an urgent need to explore new preparation strategies to simplify the process, reduce costs, and improve the electrochemical properties of Ni3S4-based electrode materials. Summary of the invention
[0011] The present invention aims to address the deficiencies of the prior art and provide a positive electrode material that can be used to prepare a supercapacitor and a preparation method thereof.
[0012] On the one hand, the positive electrode material provided by the present invention is obtained by the following preparation method, the steps are:
[0013] S1, mixing a nickel source, a cobalt source and deionized water to obtain a solution A;
[0014] S2, adding Na2S solution dropwise to solution A, stirring to obtain solution B;
[0015] S3. Solution B is subjected to a hydrothermal reaction, and after completion, the solution is cooled, and the obtained precipitate is washed and dried to obtain NiCoS-x, wherein x represents the percentage of the Co element in Ni and Co.
[0016] Further, the NiCoS-x obtained by reacting NaH2PO2 with the S3 is calcined under atmosphere protection to obtain NiCoSP-x.
[0017] Furthermore, the mass ratio of NiCoS-x to NaH2PO2 is 1:10 to 20.
[0018] Furthermore, the NiCoS-x and NaH2PO2 are calcined in a tubular furnace, with NiCoS-x at the lower port of the tubular furnace and NaH2PO2 at the upper port of the tubular furnace.
[0019] Furthermore, the heating rate during calcination is 2°C / min, the calcination temperature is 250-300°C, and the calcination time is 1-2h.
[0020] Furthermore, the nickel source is selected from one of nickel nitrate hexahydrate, nickel acetate tetrahydrate, nickel chloride hexahydrate, and nickel sulfate heptahydrate solution; the cobalt source is selected from one of cobalt nitrate hexahydrate, cobalt acetate tetrahydrate, cobalt chloride hexahydrate, and cobalt sulfate heptahydrate solution.
[0021] Furthermore, the concentration of the nickel source is 0.2-0.4 mol / L; the concentration of the cobalt source is 0.2-0.4 mol / L.
[0022] Furthermore, the concentration of the Na2S solution is 0.1-0.3 mol / L.
[0023] The working principle of the present invention is as follows: in the NiCoS-x positive electrode material, the presence of Ni and Co has a promoting effect on improving the electrochemical performance, and can improve the capacitance performance and electronic conductivity, especially the anion-cation dual-substituted nickel sulfide positive electrode material NiCoSP-x, because the electronegativity of P is less than that of S, so P replacing S can more significantly improve the electronic conductivity of the material; the simultaneous introduction of Co and P can reduce the deprotonation energy and accelerate the deprotonation process, so it is beneficial to the rapid reaction kinetics and improve OH - The adsorption / desorption ability of the material can be improved, thereby improving the electrochemical performance of the material.
[0024] The beneficial technical effects of the present invention are:
[0025] 1. The positive electrode materials NiCoS-x and NiCoSP-x are prepared by the method of the present invention. By observing their SEM photos, it is found that the two prepared materials are both two-dimensional sheet structures, which not only provides a larger specific surface area, but also helps to shorten the transmission path of ions and electrons, thereby improving the charge and discharge rate of the material.
[0026] 2. The larger specific surface area increases the number of active sites, allowing more electrolyte molecules to contact the material surface and participate in electrochemical reactions, thereby improving the energy storage capacity of the material.
[0027] 3. Due to the above structural characteristics, NiCoS-x and NiCoSP-x cathode materials performed well in electrochemical tests, with high specific capacity, good cycle stability and fast charge and discharge capabilities.
[0028] 4. Based on the excellent electrochemical properties of the positive electrode material, the NiCoS-x or NiCoSP-x positive electrode material prepared by the method of the present invention has broad application prospects in the field of supercapacitors. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a SEM photo of the NiCoS-0.5 material prepared in Example 1 of the present invention;
[0030] Figure 2 This is a SEM photo of the NiCoSP-0.5 material prepared in Example 1 of the present invention;
[0031] Figure 3 This is a SEM photo of the Ni3S4 material prepared in Comparative Example 1 of the present invention;
[0032] Figure 4 This is a SEM photo of the NiSP material prepared in Comparative Example 1 of the present invention;
[0033] Figure 5Comparison of specific capacitance curves under current density between NiCoS-x materials prepared in Example 1, Example 2, and Example 3 of the present invention and Ni3S4 and Co3S4 materials prepared in Comparative Example 1 and Comparative Example 2;
[0034] Figure 6 Comparison of specific capacitance curves under current density between the NiCoSP-x materials prepared in Examples 1, 2 and 3 of the present invention and the NiSP and CoSP materials prepared in Comparative Examples 1 and 2;
[0035] Figure 7 Cyclic voltammetry curves of the NiCoSP-x materials prepared in Examples 1, 2 and 3 of the present invention and the NiSP and CoSP materials prepared in Comparative Examples 1 and 2 at a scanning speed of 5 mV / s;
[0036] Figure 8 EIS curves of the NiCoSP-x materials prepared in Examples 1, 2 and 3 of the present invention and the NiSP and CoSP materials prepared in Comparative Examples 1 and 2. DETAILED DESCRIPTION
[0037] The following is further described in detail through specific implementation methods:
[0038] In step S4 of the following embodiment, the NiCoS-x and NaH2PO2 are placed in the tubular furnace as follows: NiCoS-x is at the lower opening of the tubular furnace, and NaH2PO2 is at the upper opening of the tubular furnace. The protective atmosphere is nitrogen or argon, and the index of the glass rotor gas flowmeter is 10 to 30.
[0039] Example 1. Preparation of positive electrode materials NiCoS-0.5 and NiCoSP-0.5
[0040] S1. Measure 3 mL of 0.2 mol / L nickel nitrate hexahydrate and cobalt nitrate hexahydrate solution, add them into 60 mL of deionized water, and stir at room temperature for 30 min to obtain solution A.
[0041] S2. Measure 15 mL of 0.1 mol / L Na2S solution and add it dropwise to solution A. The dropping speed of the Na2S solution is one drop every 10 seconds. Stir at room temperature for 60 minutes to obtain solution B.
[0042] S3, transferring solution B to a high-pressure reactor and performing a hydrothermal reaction at 120° C. for 8 h; after the reaction is completed, the solution is naturally cooled to room temperature, and the obtained precipitate is washed and dried to obtain NiCoS-0.5; wherein the washing is performed by washing with deionized water and ethanol in sequence for a total of 6 to 8 times, the drying temperature is 80° C., and the drying time is 12 h;
[0043] S4. Weigh 10 mg NiCoS-0.5 and 100 mg NaH2PO2 and calcine them under atmosphere protection. The heating rate during calcination is 2°C / min, the calcination temperature is 300°C, and the calcination time is 1 h to obtain NiCoSP-0.5.
[0044] Example 2: Preparation of positive electrode materials NiCoS-0.33 and NiCoSP-0.33
[0045] S1. 4 mL of 0.3 mol / L nickel chloride hexahydrate and 2 mL of 0.3 mol / L cobalt chloride hexahydrate solution were added into 50 mL of deionized water and stirred at room temperature for 45 min to obtain solution A.
[0046] S2. Measure 12.5 mL of 0.2 mol / L Na2S solution and add it dropwise to solution A. Stir at room temperature for 90 min. The dropping speed of Na2S solution is one drop per 15 s to obtain solution B.
[0047] S3, transferring solution B to a high-pressure reactor, and performing a hydrothermal reaction at 100° C. for 10 h; after the reaction is completed, the solution is naturally cooled to room temperature, and the obtained precipitate is washed and dried to obtain NiCoS-0.33, wherein deionized water and ethanol are used for washing in sequence for a total of 6 to 8 times, the drying temperature is 60° C., and the drying time is 24 h;
[0048] S4. Weigh 10 mg NiCoS-0.33 and 200 mg NaH2PO2 and calcine them under atmosphere protection. The heating rate during calcination is 2°C / min, the calcination temperature is 250°C, and the calcination time is 2h to obtain NiCoSP-0.33.
[0049] Example 3. Preparation of positive electrode materials NiCoS-0.67 and NiCoSP-0.67
[0050] S1. Measure 2 mL of 0.4 mol / L nickel acetate tetrahydrate and 4 mL of 0.4 mol / L cobalt acetate tetrahydrate solution, add them into 70 mL of deionized water, and stir at room temperature for 60 min to obtain solution A.
[0051] S2. Measure 10 mL of 0.3 mol / L Na2S solution and add it dropwise to solution A. Stir at room temperature for 120 min. The dropping speed of Na2S solution is one drop per 20 seconds to obtain solution B.
[0052] S3, transferring solution B to a high-pressure reactor and performing a hydrothermal reaction at 140° C. for 6 h; after the reaction is completed, the solution is naturally cooled to room temperature, and the obtained precipitate is washed and dried to obtain NiCoS-0.67; wherein the washing is performed by washing with deionized water and ethanol in sequence for a total of 6 to 8 times, the drying temperature is 80° C., and the drying time is 16 h;
[0053] S4. Weigh 10 mg NiCoS-0.33 and 120 mg NaH2PO2 and calcine them under atmosphere protection. The heating rate during calcination is 2°C / min, the calcination temperature is 280°C, and the calcination time is 1.5 h to obtain NiCoSP-0.67.
[0054] Comparative Example 1: Preparation of Ni3S4 and NiSP materials
[0055] S1. Measure 6 mL of 0.2 mol / L nickel sulfate heptahydrate solution and add it into 60 mL of deionized water. Stir at room temperature for 30 min to obtain solution A.
[0056] S2. Take 10 mL of 0.1 mol / L Na2S solution and add it dropwise to solution A. Stir at room temperature for 60 min to obtain solution B.
[0057] S3, transfer solution B to a high-pressure reactor, and perform a hydrothermal reaction at 120°C for 8 hours; after the reaction is completed, cool naturally to room temperature, wash and dry the obtained precipitate to obtain Ni3S4 material, the washing solvent is deionized water and ethanol, the washing number is 6 to 8 times, the drying temperature is 80°C, and the drying time is 12 hours;
[0058] S4. Weigh 10 mg Ni3S4 and 100 mg NaH2PO2 and calcine them under atmosphere protection. The heating rate during calcination is 2°C / min, the calcination temperature is 300°C, and the calcination time is 1 h to obtain NiSP material.
[0059] Comparative Example 2: Preparation of Co3S4 and CoSP materials
[0060] S1. Measure 6 mL of 0.2 mol / L cobalt nitrate hexahydrate solution and add it to 60 mL of deionized water. Stir at room temperature for 30 min to obtain solution A.
[0061] S2. Take 10 mL of 0.1 mol / L Na2S solution and add it dropwise to solution A. Stir at room temperature for 60 min to obtain solution B.
[0062] S3, transfer solution B to a high-pressure reactor, and perform a hydrothermal reaction at 120°C for 8 hours; after the reaction is completed, cool naturally to room temperature, wash and dry the resulting precipitate to obtain Co3S4, the washing solvents are deionized water and ethanol, the washing times are 6-8 times, the drying temperature is 80°C, and the drying time is 12 hours;
[0063] S4. Weigh 10 mg Ni3S4 and 100 mg NaH2PO2 and calcine them under atmosphere protection. The heating rate during calcination is 2°C / min, the calcination temperature is 250°C, and the calcination time is 2h to obtain CoSP material.
[0064] Preparation of single electrode: The prepared active material, carbon black and polytetrafluoroethylene (PTFE) were added to an appropriate amount of anhydrous ethanol in a mass ratio of (75:20:5) and mixed evenly, and heated to break the emulsion. The obtained slurry was coated on the nickel foam with a glass plate to form an electrode with an area of 1cm×1cm, and vacuum dried at 80℃ for 12h. The mass loading of a single electrode is about 1.5-2.0mg·cm -2 .
[0065] The SEM images of the NiCoS-0.5 and NiCoSP-0.5 materials prepared in Example 1 are shown in FIG. Figure 1 , Figure 2 As shown, it can be seen that the two prepared materials are two-dimensional sheet materials, which have a large specific surface area, which is conducive to the contact between the active material and the electrolyte, thus giving them excellent electrochemical properties.
[0066] The SEM photos of Ni3S4 and NiSP materials prepared in the comparative example are as follows: Figure 3 , Figure 4 As shown, it can be seen that the two prepared materials are one-dimensional spherical materials, which have a smaller specific surface area than two-dimensional sheet materials, resulting in fewer reaction active sites for active substances.
[0067] The performance differences of the materials obtained from the above embodiments and comparative examples are shown in Table 1 below.
[0068] Table 1 Performance differences between the materials obtained in the examples and comparative examples
[0069]
[0070] It can be seen from the data in Table 1 above that the NiCoS-x and NiCoSP-x positive electrode materials provided by the present invention perform well in electrochemical tests, have excellent specific capacity, good cycle stability and fast charge and discharge capabilities. Based on this, NiCoS-x or NiCoSP-x positive electrode materials can be applied to the field of supercapacitors and meet the performance requirements of supercapacitors.
Claims
1. A method for preparing a positive electrode material, characterized in that: The following steps are involved: S1, mixing a nickel source, a cobalt source and deionized water to obtain a solution A; S2, adding Na2S solution dropwise to solution A, stirring to obtain solution B; S3. Solution B is subjected to a hydrothermal reaction, and after completion, the solution is cooled, and the obtained precipitate is washed and dried to obtain NiCoS-x, wherein x represents the percentage of the Co element in Ni and Co.
2. The method for preparing a positive electrode material according to claim 1, characterized in that: The NiCoS-x obtained by combining NaH2PO2 and S3 is calcined under atmosphere protection to obtain NiCoSP-x.
3. The method for preparing a positive electrode material according to claim 2, characterized in that: The mass ratio of NiCoS-x to NaH2PO2 is 1:10-20.
4. The method for preparing a positive electrode material according to claim 2, characterized in that: The NiCoS-x and NaH2PO2 are calcined in a tubular furnace, with NiCoS-x at the lower port of the tubular furnace and NaH2PO2 at the upper port of the tubular furnace.
5. The method for preparing a positive electrode material according to claim 2, characterized in that: The heating rate during calcination is 2°C / min, the calcination temperature is 250-300°C, and the calcination time is 1-2h.
6. A method for preparing a positive electrode material according to any one of claims 1 to 5, characterized in that: The nickel source is selected from one of nickel nitrate hexahydrate, nickel acetate tetrahydrate, nickel chloride hexahydrate, and nickel sulfate heptahydrate solution; the cobalt source is selected from one of cobalt nitrate hexahydrate, cobalt acetate tetrahydrate, cobalt chloride hexahydrate, and cobalt sulfate heptahydrate solution.
7. A method for preparing a positive electrode material according to any one of claims 1 to 5, characterized in that: The concentration of the nickel source is 0.2-0.4 mol / L; the concentration of the cobalt source is 0.2-0.4 mol / L.
8. A method for preparing a positive electrode material according to any one of claims 1 to 5, characterized in that: The concentration of the Na2S solution is 0.1-0.3 mol / L.
9. A positive electrode material, characterized in that: The method is prepared by any one of claims 1 to 5.
10. The positive electrode material according to claim 9 is used in preparing a supercapacitor.
Citation Information
Patent Citations
A preparation method of flower-shaped nickel sulfide material and its application in supercapacitors
CN105489390B
Application of nickel sulfide / carbon nanotube flexible composite thin film materials in supercapacitors
CN109872881B
Preparation method of nano-nickel sulfide / nitrogen-doped porous carbon composite material for supercapacitors
CN111333129B
Method for synthesizing MXene / nickel-cobalt sulfide electrode material by one-pot method
CN117275962A